Anxiety level of first-year medical students from a private university in Peru in times of Covid-19: Nivel de ansiedad de estudiantes de medicina de primer año de una universidad privada del Perú en tiempos de Covid-19 - Saravia-Bartra, María M. (2020)
Introduction: The current pandemic due to a new coronavirus (SARS-Cov-2) has claimed the health and lives of many people worldwide. This has a negative impact on the mental health of health personnel, which includes medical students. Objective: To determine the degree of anxiety present in first-year medical students from a private university, Lima-Peru. Methods: The sample consisted of 57 students from private university in Lima Perú. The scale was applied to measure Generalized Anxiety Disorder-7 (GAD-7). The data were analyzed using frequency and contingency tables, in addition bivariate analysis was performed applying the statistical tests X2 and Student's t. Results: 75.4% of the medical students manifested some degree of anxiety. A statistically significant association was found between female sex and anxiety (p = 0.045). Likewise, there was no association between the variables age and anxiety (p = 0.058). Conclusion: First-year medical students showed high levels of anxiety during the current pandemic, with women being among those who anxiety occurs more frequently. The development of intervention strategies in university centers for the care of mental health of health sciences students is timely.